Characterization of in-barn heat processed swine mortalities - Ramirez, Brett C.; Jeon, Ryan; Stender, Dave R.; Kohl, Kris D.; Rademacher, Chris J.; Brown, Justin T.; Mogler, Dwight (Frontiers in Veterinary Science, 2023)
In-barn heat processing of mass swine mortalities to inactivate pathogens could facilitate more carcass disposal options and reduce the risk of pathogen spread in the event of a foreign animal disease (FAD) outbreak. A 12.2 × 12.2 × 2.4 m (W × L × H) heat processing room was created using a temporary wall inside a de-commissioned commercial gestation barn in northwest Iowa. Eighteen swine carcasses (six per group) divided into three weight groups (mean ± SD initial carcass weights: 31.8 ± 3.3, 102.7 ± 8.1, and 226.3 ± 27.6 kg) were randomly assigned a location inside the room. Three carcasses per weight group were placed directly on concrete slats and on a raised platform. One carcass per weight group and placement (n=6) was instrumented with five temperature sensors, inserted into the brain, pleura, peritoneal, ham, and bone marrow of the femur, and a sensor was attached directly to the skin surface. Environmental conditions (ambient and room) and carcass temperatures were collected at 15-min intervals. Carcasses were subjected to an average room temperature of 57.3 ± 1.2°C for 14 days. The average (±SD) reduction from initial weight for the carcasses on slats was 45.0 ± 4.70% (feeder), 33.0 ± 8.30% (market), and 34.0 ± 15.80% (sow), and for the carcasses on a raised platform, it was 39.0 ± 6.80% (feeder), 49.0 ± 11.30% (market), and 45.0 ± 6.70% (sow). There was a significant interaction between carcass placement (slats and raised) and carcass weight loss for the market weight group. When average carcass surface temperature was at 40.6, 43.3, and 46.1°C (data grouped for analysis), the average internal carcass temperature for most measurement locations was significantly different across carcass weight groups and between the carcasses on a raised platform and those on slats. This preliminary analysis of carcass weight loss, leachate production, and temperature variation in carcasses of different sizes can be used for planning and evaluating mass swine mortality management strategies.